Inhibitors of Glutamate Dehydrogenase Block Sodium-Dependent Glutamate Uptake in Rat Brain Membranes - Whitelaw, Brendan S.; Robinson, Michael B. (Frontiers in Endocrinology, 2013)
We recently found evidence for anatomic and physical linkages between the astroglial Na+-dependent glutamate transporters (GLT-1/EAAT2 and GLAST/EAAT1) and mitochondria. In these same studies, we found that the glutamate dehydrogenase (GDH) inhibitor, epigallocatechin-monogallate (EGCG), inhibits both glutamate oxidation and Na+-dependent glutamate uptake in astrocytes. In the present study, we extend this finding by exploring the effects of EGCG on Na+-dependent L-[3H]-glutamate (Glu) uptake in crude membranes (P2) prepared from rat brain cortex. In this preparation, uptake is almost exclusively mediated by GLT-1. EGCG inhibited L-[3H]-Glu uptake in cortical membranes with an IC50 value of 230 µM. We also studied the effects of two additional inhibitors of GDH, hexachlorophene (HCP) and bithionol (BTH). Both of these compounds also caused concentration-dependent inhibition of glutamate uptake in cortical membranes. Pre-incubating with HCP for up to 15 min had no greater effect than that observed with no pre-incubation, showing that the effects occur rapidly. HCP decreased the Vmax for glutamate uptake without changing the Km, consistent with a non-competitive mechanism of action. EGCG, HCP, and BTH also inhibited Na+-dependent transport of D-[3H]-aspartate (Asp), a non-metabolizable substrate, and [3H]-γ-aminobutyric acid (GABA). In contrast to the forebrain, glutamate uptake in crude cerebellar membranes (P2) is likely mediated by GLAST (EAAT1). Therefore, the effects of these compounds were examined in cerebellar membranes. In this region, none of these compounds had any effect on uptake of either L-[3H]-Glu or D-[3H]-Asp, but they all inhibited [3H]-GABA uptake. Together these studies suggest that GDH is preferentially required for glutamate uptake in forebrain as compared to cerebellum, and GDH may be required for GABA uptake as well. They also provide further evidence for a functional linkage between glutamate transport and mitochondria.